Comparative transcriptome analysis of purple-fleshed sweet potato and its yellow-fleshed mutant provides insight into the transcription factors involved in anthocyanin biosynthesis in tuberous root - Dong, Wen; Tang, Linfei; Peng, Yali; Qin, Yuzhi; Lin, Yuan; Xiong, Xingyao; Hu, Xinxi (Frontiers in Plant Science, 2022)
In various plant species, many transcription factors (TFs), such as MYB, bHLH, and WD40, have been identified as regulators of anthocyanin biosynthesis in underground organs. However, the regulatory elements of anthocyanin biosynthesis in the tuberous roots of sweet potato have not been elucidated yet. Here, we selected the purple-fleshed sweet potato cultivar “Zhezi1” (ZZP) and its spontaneous yellow-fleshed mutant “Xinli” (XLY) to investigate the regulatory mechanism of the anthocyanin biosynthesis in the tuberous roots of sweet potato. By analyzing the IbMYB1 genotype in ZZP and XLY, we found that the IbMYB1-2, a MYB TF involved in anthocyanin biosynthesis, was missing in the XLY genome, which might lead to an extreme decrease in anthocyanins in XLY. A comparative transcriptome analysis of ZZP and XLY was conducted to find the TFs involved in anthocyanin biosynthesis in ZZP and XLY. The anthocyanin structural genes were significantly enriched among the differentially expressed genes. Moreover, one MYB activator (IbMYB1), one bHLH (IbbHLH2), three WRKY activator candidates (IbWRKY21, IbWRKY24, and IbWRKY44), and two MYB repressors (IbMYB27 and IbMYBx-ZZ) were highly expressed in ZZP accompanied with anthocyanin structural genes. We also tested the expression of these TFs in 6 purple- and 2 orange-fleshed sweet potato cultivars. Interestingly, most of these TFs were significantly positively correlated with anthocyanin contents in these cultivars. The function of the anthocyanin biosynthesis repression of IbMYB27 and IbMYBx-ZZ was verified through transient co-transformation with IbMYB1 into tobacco leaves. Further functional verification of the above TFs was conducted by Y2H, BiFC, and dual-luciferase assays. These tests showed that the MYB-bHLH-WD40/MYB-bHLH-WD40-WRKY complex activated the promoter of anthocyanin structural gene IbDFR and promoters for IbWRKY44, IbMYB27, and IbMYBx-ZZ, indicating reinforcement and feedback regulation to maintain the level of anthocyanin accumulation in the tuberous roots of purple-fleshed sweet potato. These results may provide new insights into the regulatory mechanism of anthocyanin biosynthesis and accumulation in underground organs of sweet potatoes.